The Routledge Companion to Global Renaissance Art - Campbell, Stephen J.; Porras, Stephanie (Routledge Art History and Visual Studies Companions, 2024)
This companion examines the global Renaissance through object-based case studies of artistic production from Africa, Asia, the Americas, and Europe in the early modern period. The international group of contributors take an art historical approach characterized by close analysis of form and meaning as well as function, and a focus on questions of crosscultural dialogue and adaptation. Seeking to de-emphasize the traditional focus on Europe, this book is a critical guide to the literature and the state of the field. Chapters outline new questions and agendas while pushing beyond familiar material. Main themes include workshops, the migrations of artists, objects, technologies, diplomatic gifts, imperial ideologies, ethnicity and indigeneity, sacred spaces and image cults, as well as engaging with the open questions of "the Renaissance" and "the global." This will be a useful and important resource for researchers and students alike and will be of interest to scholars working in art history, visual culture, material culture, and Renaissance studies. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license